Phytochemical profiling as a solution to palliate disinfectant limitations. Issue 9 (20th October 2016) - Malheiro, J.; Gomes, I.; Borges, A.; Bastos, M. M. S. M.; Maillard, J.-Y.; Borges, F.; Simões, M.
Abstract: The indiscriminate use of biocides for general disinfection has contributed to the increased incidence of antimicrobial tolerant microorganisms. This study aims to assess the potential of seven phytochemicals (tyrosol, caffeic acid, ferulic acid, cinnamaldehyde, coumaric acid, cinnamic acid and eugenol) in the control of planktonic and sessile cells of Staphylococcus aureus and Escherichia coli . Cinnamaldehyde and eugenol showed antimicrobial properties, minimum inhibitory concentrations of 3–5 and 5–12 mM and minimum bactericidal concentrations of 10–12 and 10–14 mM against S. aureus and E. coli, respectively. Cinnamic acid was able to completely control adhered bacteria with effects comparable to peracetic acid and sodium hypochlorite and it was more effective than hydrogen peroxide (all at 10 mM). This phytochemical caused significant changes in bacterial membrane hydrophilicity. The observed effectiveness of phytochemicals makes them interesting alternatives and/or complementary products to commonly used biocidal products. Cinnamic acid is of particular interest for the control of sessile cells.